Further Validation of Workplace Spirituality Scale in an Eastern Context - Shrestha, Arjun Kumar (Journal of Business and Management Research, 2016)
Several scales for measuring workplace spirituality (WPS) are available. However, a majority of the available scales were developed in the Western context that may not be generalizable in an Eastern context. Petchsawang and Duchon (2009) developed a 22-item, four dimensional WPS scale with a sample from an Eastern Buddhist-centric culture for capturing WPS in an Eastern context. The purpose of this study was to assess the generalizability, dimensionality, and convergent and discriminant validity of this scale in another Eastern context, which has a strong tradition of Hindu culture. Confirmatory Factor Analyses were conducted on the data collected from 211 individuals, and results supported the four dimensions of the scale. Other statistical analyses demonstrated convergent and discriminant validity of the scale. Limitations of the study are highlighted, and suggestions for future research are discussed. Journal of Business and Management Studies Vol.1(1) 2016: 1-13